Conductive composite current collector, preparation method thereof and battery

By introducing a support layer, a metal layer and a PTC primer into the composite fluid of the battery, the problem of difficult to take into account the conductivity and safety performance of the traditional composite fluid is solved, and the rate performance, cycle performance and safety performance of the battery are significantly improved.

CN119581570AActive Publication Date: 2025-03-07SHENZHEN HANKE NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510112102.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-03-07
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The conductivity and safety performance of traditional composite fluids are difficult to take into account, which affects the rate performance, cycle performance and safety performance of the battery.

Method used

A conductive composite fluid collecting is provided, including a support layer, a metal layer and a PTC primer layer. The support layer consists of a polymer base film and conductive fibers dispersed therein, a metal layer is arranged on the surface of the support layer, and the PTC undercoat layer is composed of a conductive polymer and a conductive agent, and is coated on the surface of the metal layer.

Benefits of technology

The conductive and safety performance of the conductive composite fluid is improved, the rate performance, cycle performance and safety performance of the battery are enhanced, and the probability of the battery being thermally out of control at high temperatures is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581570A_ABST
    Figure CN119581570A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, in particular to a conductive composite current collector, a preparation method thereof and a battery. The conductive composite current collector comprises a supporting layer, a metal layer arranged on at least one surface of the supporting layer and a PTC (Positive Temperature Coefficient) bottom coating arranged on the surface, far away from the supporting layer, of the metal layer, the supporting layer comprises a polymer base membrane and conductive fibers dispersed in the polymer base membrane; the PTC undercoat layer includes a conductive polymer and a conductive agent dispersed in the conductive polymer. The conductive composite current collector provided by the invention is high in conductivity and excellent in safety, the probability of thermal runaway of the battery at a high temperature is effectively reduced, and the rate capability and the cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a conductive composite current collector, a preparation method thereof, and a battery. Background Art

[0002] The large-scale use of traditional fossil fuels has led to increasingly serious problems such as resource shortages and environmental pollution. It is of great significance to accelerate the transformation of energy structure and develop clean and renewable new energy. Among them, secondary batteries such as lithium-ion batteries are widely used in 3C products, energy storage systems and power batteries due to their high energy density, long cycle life, good rate performance and low cost. As secondary batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance.

[0003] The pole piece is an important component of the secondary battery. The pole piece includes a current collector, which can be a metal foil or a composite current collector. Compared with metal foil, the composite current collector is lighter at the same thickness, and the energy density of the assembled secondary battery is higher. However, it is difficult to balance the conductivity and safety performance of the traditional composite current collector. Summary of the invention

[0004] Based on this, it is necessary to provide a conductive composite current collector and a preparation method thereof and a battery to solve the problem that it is difficult to balance the conductive performance and safety performance of the traditional composite current collector.

[0005] The above-mentioned purpose of the present application is achieved through the following technical solutions:

[0006] In a first aspect of the present application, a conductive composite current collector is provided, comprising a support layer, a metal layer disposed on at least one surface of the support layer, and a PTC primer layer disposed on a surface of the metal layer away from the support layer;

[0007] The support layer includes a polymer base film and conductive fibers dispersed in the polymer base film;

[0008] The PTC primer layer includes a conductive polymer and a conductive agent dispersed in the conductive polymer.

[0009] In some embodiments, the conductive fiber comprises a fiber and a conductive layer supported on the fiber;

[0010] The fibers include at least one of carbon fibers, conductive polymer fibers, and metal fibers;

[0011] The material of the conductive layer includes at least one of semi-liquid metal, high entropy alloy and Mxene material.

[0012] In some embodiments, the material of the polymer-based film includes at least one of polyethylene, polypropylene, polyimide, polyvinyl chloride, polystyrene, polyvinyl alcohol, polyethylene terephthalate, and polybutylene terephthalate.

[0013] In some embodiments, the mass ratio of the polymer-based film to the conductive fiber is 100:(1-30).

[0014] In some embodiments, the thickness of the support layer is 4 μm-10 μm.

[0015] In some embodiments, the conductive polymer includes at least one of poly (3-hexylthiophene), poly (3-dodecylthiophene), poly (3-dodecylthiophene-3-hexyl-3-triethylene glycol), and poly (3-octylpyrrole): poly (styrene sulfonic acid).

[0016] In some embodiments, the conductive agent includes at least one of carbon black, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers, and metal particles.

[0017] In some embodiments, the mass ratio of the conductive polymer to the conductive agent is 100:(1-50).

[0018] In some embodiments, the thickness of the PTC primer layer is 0.5 μm to 3 μm.

[0019] In some embodiments, the conductivity of the PTC primer layer at room temperature is 10 S / cm to 40 S / cm.

[0020] In some embodiments, the material of the metal layer includes at least one of stainless steel, copper, nickel and aluminum.

[0021] In some embodiments, the thickness of the metal layer is 0.5 μm to 4 μm.

[0022] In some embodiments, the support layer further comprises a tab connector, the tab connector comprising an embedded part and an exposed part connected to the embedded part, the embedded part is embedded in the polymer base film, and the exposed part is located at the periphery of the polymer base film;

[0023] The area of ​​the metal layer corresponding to the exposed part is an inactive area, the area outside the inactive area is an active area, and the PTC primer layer is located on the active area.

[0024] In some embodiments, the material of the tab connector includes at least one of stainless steel, copper, nickel and aluminum.

[0025] In some embodiments, the thickness of the embedded part is smaller than the thickness of the exposed part, and the thickness of the exposed part is not smaller than the thickness of the polymer-based film.

[0026] In some embodiments, the width of the embedded part is 2 cm to 12 cm, and the width of the exposed part is 2 cm to 8 cm.

[0027] In a second aspect of the present application, a method for preparing the conductive composite current collector as described above is provided, comprising the following steps:

[0028] The polymer resin and the conductive fibers are melt-blended and the obtained mixture is cast and molded, wherein the polymer resin forms a polymer base film and the conductive fibers are dispersed in the polymer base film to obtain a support layer;

[0029] forming a metal layer on at least one surface of the support layer;

[0030] A dispersion containing a conductive polymer and a conductive agent is coated on the metal layer, and the PTC primer layer is obtained after drying.

[0031] In a third aspect of the present application, a battery is provided, comprising the conductive composite current collector as described above.

[0032] In some embodiments, the battery further comprises a positive electrode sheet, wherein the positive electrode sheet comprises the conductive composite current collector and a positive electrode active layer disposed on at least one surface of the conductive composite current collector;

[0033] The positive electrode active layer includes a positive electrode active material, the positive electrode active material includes a core and a coating layer coating the core, the core includes at least one of a lithium transition metal oxide and an olivine-structured lithium-containing phosphate, and the coating layer includes a relaxor ferroelectric material.

[0034] This application has at least the following beneficial effects:

[0035] The conductive composite current collector provided by the present application includes a support layer, a metal layer and a PTC primer layer. Among them, conductive fibers are dispersed in the polymer base film of the support layer, which not only improves the mechanical strength of the conductive composite current collector, but also improves the conductivity of the support layer, reduces the overcurrent heating problem existing in the working process of high rate and high current, and ensures the stable performance of the electrochemical performance of the battery. The PTC primer layer adopts a conductive polymer as a matrix, and uses a conductive agent to construct a conductive network, which effectively improves the conductivity of the PTC primer layer, and is conducive to improving the adhesion and peeling strength between the conductive composite current collector and the active material, thereby improving the cycle stability of the battery. At the same time, the PTC primer layer is arranged on the surface of the metal layer, which can effectively inhibit the generation of sharp burrs of the metal layer during the needle puncture process, and can stimulate the PTC effect under high temperature conditions to significantly increase the resistance value, thereby inhibiting the short-circuit current and improving the safety of the battery. Therefore, the conductive composite current collector provided by the present application has high conductivity and excellent safety, effectively reduces the probability of thermal runaway of the battery at high temperature, and is conducive to improving the rate performance and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0037] Figure 1 Schematic diagram of the structure of a conductive composite current collector A100 in one embodiment of the present application;

[0038] Figure 2 Schematic diagram of the structure of a conductive composite current collector B200 in another embodiment of the present application;

[0039] Figure 3 Schematic diagram of a process for preparing a conductive composite current collector in one embodiment of the present application.

[0040] Figure numerals: 100, conductive composite current collector A; 110, support layer A; 120, metal layer A; 130, PTC primer layer A; 200, conductive composite current collector B; 210, support layer B; 211, tab connector; 211a, exposed part; 211b, embedded part; 220, metal layer B; 230, PTC primer layer B; X, second direction; Z, first direction. DETAILED DESCRIPTION

[0041] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0043] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. "At least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0044] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.

[0045] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0046] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.

[0047] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0048] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.

[0049] The composite current collector includes a polymer layer and a metal layer formed on both surfaces of the polymer layer, thereby forming a sandwich structure of "metal layer / polymer layer / metal layer". Compared with metal foil, at the same thickness, the composite current collector is lighter, the energy density of the assembled secondary battery is higher, and it exhibits higher safety performance.

[0050] However, the poor conductivity of the polymer layer in the composite current collector makes it easy to cause heat accumulation when a large current passes through it, thereby causing battery performance degradation and even thermal runaway. At the same time, during the needle puncture process, it is still difficult to avoid the generation of sharp burrs on the metal layer in the composite current collector. The direction of these burrs is uncontrollable, which can easily cause a short circuit inside the battery cell and trigger a violent exothermic reaction, and cause thermal runaway of the battery. Therefore, it is difficult to balance the conductivity and safety performance of the traditional composite current collector, which affects the rate performance, cycle performance and safety performance of the battery.

[0051] Based on this, in the first aspect of the present application, a conductive composite current collector is provided, which aims to improve the conductivity and safety performance of the conductive composite current collector, thereby improving the rate performance, cycle performance and safety performance of the battery.

[0052] See also Figure 1 , which is a schematic diagram of the structure of a conductive composite current collector A100 in one embodiment of the present application. Figure 1 As shown, the conductive composite current collector A100 includes a support layer A110, a metal layer A120 disposed on two opposite surfaces of the support layer A110, and a PTC primer layer A130 disposed on a surface of the metal layer A120 away from the support layer A110;

[0053] The support layer A110 includes a polymer base film and conductive fibers dispersed in the polymer base film;

[0054] The PTC undercoating layer A130 includes a conductive polymer and a conductive agent dispersed in the conductive polymer.

[0055] In this application, the positive temperature coefficient (PTC) effect refers to the phenomenon that the resistance of a material increases with increasing temperature.

[0056] The conductive composite current collector A100 provided in the present application includes a support layer A110, a metal layer A120 and a PTC bottom coating A130. Among them, conductive fibers are dispersed in the polymer base film of the support layer A110, which not only improves the mechanical strength of the conductive composite current collector, but also improves the conductivity of the support layer A110, reduces the overcurrent heating problem existing in the high-rate and high-current working process, and ensures the stable performance of the electrochemical performance of the battery. The PTC bottom coating A130 uses a conductive polymer as a matrix and uses a conductive agent to construct a conductive network, which effectively improves the conductivity of the PTC bottom coating A130, and is conducive to improving the adhesion and peeling strength between the conductive composite current collector and the active material, thereby improving the cycle stability of the battery. At the same time, the PTC bottom coating A130 is arranged on the surface of the metal layer A120, which can effectively inhibit the generation of sharp burrs of the metal layer A120 during the acupuncture process, and can stimulate the PTC effect under high temperature conditions to significantly increase the resistance value, thereby inhibiting the short-circuit current and improving the safety of the battery. Therefore, the conductive composite current collector A100 provided in the present application has high conductivity and excellent safety, which effectively reduces the probability of thermal runaway of the battery at high temperature and is beneficial to improving the rate performance and cycle performance of the battery.

[0057] In some embodiments, the conductive fiber comprises a fiber and a conductive layer supported on the fiber;

[0058] The fibers include at least one of carbon fibers, conductive polymer fibers, and metal fibers;

[0059] The material of the conductive layer includes at least one of semi-liquid metal, high entropy alloy and Mxene material.

[0060] Therefore, by forming a conductive layer on the fiber surface using a semi-liquid metal, high entropy alloy or Mxene material with high conductivity, the conductivity of the conductive fiber can be improved, so that the conductivity of the support layer A110 is further improved.

[0061] In the present application, semi-liquid metal refers to a metal material or alloy material that is liquid or semi-solid at room temperature or near room temperature, has high permeability, strong adhesion, excellent ductility and good conductivity, effectively improves the conductivity of the conductive fiber, and improves the bonding strength between the conductive fiber and the polymer base film.

[0062] In some embodiments, the semi-liquid metal includes at least one of Cu-Ga-In and Fe-Ga-In. Further, the semi-liquid metal may be a Cu-Ga-In alloy.

[0063] In some specific examples, when the conductive layer uses semi-liquid metal, the conductive fiber can be prepared by the following method: immersing the fiber in propylene glycol methyl ether acetate (PMA) for 5s to 10s, taking it out and drying it in the air to form a PMA coating on the fiber surface; covering the substrate with a layer of Cu-Ga-In alloy, and placing the fiber with the PMA coating on the surface of the Cu-Ga-In alloy, and utilizing the adsorption properties between the Cu-Ga-In alloy and PMA to transfer the Cu-Ga-In alloy to the fiber surface.

[0064] In the present application, high-entropy alloys (HEA) materials are alloy materials composed of at least five metal elements in an equiatomic ratio or a nearly equiatomic ratio; different from traditional alloys with one or two metal elements as the dominant components, multiple metal elements in HEA materials jointly occupy a dominant position, the mixing entropy is relatively high, and they usually present a simple crystal structure (such as face-centered cubic structure, body-centered cubic structure or close-packed hexagonal structure) and have microstructural uniformity, so they exhibit excellent fracture resistance, tensile strength, corrosion resistance and oxidation resistance, and play a good protective role on the fiber while improving conductivity.

[0065] In some embodiments, the high entropy alloy includes at least five of iron (Fe), cobalt (Co), nickel (Ni), chromium (Cr), manganese (Mn), aluminum (Al), copper (Cu), titanium (Ti), vanadium (V), yttrium (Y) and tantalum (Ta). Further, the high entropy alloy includes at least five of iron (Fe), nickel (Ni), cobalt (Co), chromium (Cr), aluminum (Al), vanadium (V), yttrium (Y) and tantalum (Ta). Further, the high entropy alloy is at least one of AlCrFeNiV, NiCoCrAlY and NiCoCrAlYTa.

[0066] In some specific examples, when the conductive layer is made of high entropy alloy, the conductive fiber can be prepared by the following method: placing the fiber in a cavity, evacuating the cavity to 2×10 -5 Pa~8×10 -5 Pa, Ar is introduced at 60sccm~100sccm, the working gas pressure is 0.1Pa~1Pa, the sputtering power is 20W~50W, the sputtering target is a high entropy alloy, and a 20nm~100nm thick high entropy alloy coating is formed on the fiber surface by magnetron sputtering.

[0067] In some embodiments, MXene material is a new type of two-dimensional nanolayered material with good flexibility, high specific surface area, high mechanical strength and excellent conductivity, which is also beneficial to improve the conductivity of conductive fibers.

[0068] In some embodiments, the molecular formula of the Mxene material is M n+1 X n T x ; wherein n=1, 2, 3; M represents a transition metal element, M includes at least one of Ti, Ta, Mo, V, Sr and Zr; X represents at least one of carbon and nitrogen; T represents a surface active functional group, T includes at least one of -OH, -F and -O, x represents the number of T, x>0. Further, MXene materials include Ti3C2T x 、Ti2CT x 、Ti3CNT x 、Ta4C3T x 、V2CT x 、V3C2T x 、Mo2CT x and Mo2TiC2T x At least one of .

[0069] In some specific examples, when the conductive layer uses Mxene material, the conductive fiber can be prepared by the following method: disperse the Mxene material in N,N-dimethylformamide (DMF) to obtain a dispersion A with a concentration of 75 mg / mL~250 mg / mL; disperse the fiber in DMF, ultrasonically disperse for 2h~4h, and obtain a dispersion B with a concentration of 20 mg / mL~40 mg / mL; add thermoplastic polyurethane elastomer (TPU) to dispersion A and dispersion B in an amount of 150 mg / mL, stir for 2h~4h, and obtain spinning solution A and spinning solution B; obtain the fiber coated with Mxene material by coaxial wet spinning technology, the outer needle diameter is 10%~30% of the inner needle diameter, the outer needle extrusion speed is 0.2mL / min, and the inner needle extrusion speed is 0.6mL / min; the spun fiber is cured in a coagulation bath containing 8% isopropyl alcohol (IPA) for 30min and dried naturally.

[0070] In some embodiments, the carbon fiber includes at least one of filament carbon fiber, chopped carbon fiber, carbon nanofiber (CNF), and vapor grown carbon fiber (VGCF).

[0071] In some embodiments, the conductive polymer fiber includes at least one of polyacetylene (PA) fiber, polypyrrole (PPy) fiber, poly 3-hexylthiophene (P3HT) fiber, poly(3-dodecylthiophene) (P3DDT) fiber, poly(3-dodecylthiophene-3-hexyl-3-triethylene glycol) (PDDHEO) fiber, poly(3-octylpyrrole):poly(styrene sulfonic acid) (P3OPy:PSS) fiber, and polyphenylene furandione (PBFDO) fiber.

[0072] In some embodiments, the metal fiber includes at least one of copper fiber, nickel fiber, aluminum fiber and silver fiber. Further, the metal fiber may be silver nanofiber (Ag NF).

[0073] In some embodiments, in the conductive fiber, the thickness of the conductive layer is 20 nm to 200 nm, including but not limited to 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm or 200 nm.

[0074] In some embodiments, the conductive fibers have an aspect ratio of 2 to 50,000, including but not limited to 2, 5, 10, 50, 100, 500, 1000, 5000, 10000, 20000, 30000, 40000, or 50000.

[0075] In some embodiments, the diameter of the conductive fiber is 0.02 μm to 50 μm, including but not limited to 0.02 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm.

[0076] In some embodiments, the length of the conductive fibers is 0.1 mm to 1 mm, including but not limited to 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm.

[0077] In some embodiments, the material of the polymer-based film includes at least one of polyethylene (PE), polypropylene (PP), polyimide (PI), polyvinyl chloride (PVC), polystyrene (PS), polyvinyl alcohol (PVA), polyethylene terephthalate (PET), and polybutylene terephthalate (PBT). Further, the material of the polymer-based film includes at least one of polypropylene (PP), polyimide (PI), and polyethylene terephthalate (PET).

[0078] In some embodiments, the mass ratio of the polymer-based film to the conductive fiber is 100: (1-30), including but not limited to 100: 1, 100: 2, 100: 5, 100: 8, 100: 10, 100: 12, 100: 15, 100: 18, 100: 20, 100: 22, 100: 25, 100: 28 or 100: 30. Further, the mass ratio of the polymer-based film to the conductive fiber is 100: (5-15).

[0079] Adding an appropriate amount of conductive fibers can build a complete conductive network in the polymer base film, improve the heat generation problem caused by large current transportation, and thus provide a guarantee for the stable performance of the battery. At the same time, it can also play a certain toughening role and improve the tensile strength of the conductive composite current collector, so that it can play a role in buffering stress and maintaining structural stability during the preparation and operation of the battery, thereby improving the battery's cycle performance.

[0080] In some embodiments, the thickness of the support layer A110 is 4 μm to 10 μm, including but not limited to 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0081] In this application, if Figure 1 As shown, the support layer A110 has two surfaces opposite to each other in its thickness direction, and the metal layer A120 is disposed on the two opposite surfaces of the support layer A110. However, the present application is not limited thereto, and in some other examples, the metal layer A120 may also be disposed on any one of the two opposite surfaces of the support layer A110.

[0082] In some embodiments, the material of the metal layer A120 includes at least one of stainless steel, copper, nickel and aluminum;

[0083] In some embodiments, the thickness of the metal layer A120 is 0.5 μm to 4 μm, including but not limited to 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm or 4 μm.

[0084] In the present application, the metal layer A120 has two surfaces opposite to each other in its thickness direction, one of which is close to the support layer A110 and the other is far from the support layer A110. The PTC primer layer A130 is disposed on the surface of the metal layer A120 far from the support layer A110.

[0085] In some embodiments, the conductive polymer includes at least one of poly (3-hexylthiophene) (P3HT), poly (3-dodecylthiophene) (P3DDT), poly (3-dodecylthiophene-3-hexyl-3-triethylene glycol) (PDDHEO), and poly (3-octylpyrrole): poly (styrene sulfonic acid) (P3OPy:PSS).

[0086] Traditional PTC primers usually use polymers such as polyethylene (PE), polypropylene (PP) and polyvinylidene fluoride (PVDF) as the matrix, and use the high-temperature phase change mechanism of these polymers to destroy the conductive channel to form the PTC effect. However, these PTC primers usually respond slowly to temperature changes. After the temperature returns to the operating temperature, the conductive channel cannot be effectively restored, which reduces the safety and cycle stability of the composite current collector.

[0087] The conductive polymer used in the present application is doped with anions, so that the PTC bottom coating A130 has good electrical conductivity, which is conducive to reducing the amount of conductive agent added in the PTC bottom coating A130, so that the PTC effect produced by the PTC bottom coating A130 is more significant. At the same time, the above-mentioned conductive polymer realizes the PTC effect based on the doping and dedoping mechanism of anions. The conductive polymer will undergo dedoping of anions at the high temperature critical temperature, thereby causing the polymer main chain to be disordered and causing a sharp increase in the resistance value. This process does not involve changes in the main chain of the conductive polymer and has a certain reversibility. In addition, the introduction of the conductive agent also promotes the doping and dedoping reactions of anions to a certain extent. Therefore, the PTC bottom coating A130 of the present application responds more quickly to temperature changes and has a stronger reversibility of the reaction, so that the conductive composite current collector has both excellent conductivity and safety.

[0088] In some embodiments, the conductive agent includes at least one of carbon black, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers, and metal particles. The metal particles may be at least one of iron powder, copper powder, nickel powder, aluminum powder, zinc powder, and silver powder. Further, the conductive agent includes but is not limited to at least one of Super-P (SP), Super-C (SC), KS-6, SFG-6, vapor grown carbon fiber (VGCF), carbon nanotubes (CNT), and graphene.

[0089] In some embodiments, the particle size of the conductive agent is 20 nm to 100 nm, including but not limited to 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm.

[0090] In some embodiments, the mass ratio of the conductive polymer to the conductive agent is 100:(1-50), including but not limited to 100:1, 100:5, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45 or 100:50.

[0091] In some embodiments, the PTC primer coating A130 further includes a binder having a mass fraction of 1% to 10%, and the mass fraction of the binder includes but is not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%; the binder includes at least one of polyvinylidene fluoride (PVDF), sodium alginate (SA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), hydrogenated nitrile rubber (HNBR), polytetrafluoroethylene (PTFE) and polyacrylic acid (PAA).

[0092] In some embodiments, the thickness of the PTC primer layer A130 is 0.5 μm to 3 μm, including but not limited to 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.

[0093] In some embodiments, the conductivity of the PTC primer coating A130 at room temperature is 10 S / cm to 40 S / cm, including but not limited to 10 S / cm, 15 S / cm, 20 S / cm, 25 S / cm, 30 S / cm, 35 S / cm or 40 S / cm.

[0094] In the present application, the conductivity of the PTC primer coating at room temperature can be tested by the following method: placing the conductive composite current collector on the workbench of a four-probe conductivity tester, making the probes accurately contact the PTC primer coating, and directly reading the conductivity data of the PTC primer coating at room temperature.

[0095] See also Figure 2 , which is a schematic diagram of the structure of a conductive composite current collector B200 in another embodiment of the present application. Figure 2 As shown, the conductive composite current collector B200 includes a support layer B210, a metal layer B220 disposed on two opposite surfaces of the support layer B210, and a PTC primer layer B230 disposed on a surface of the metal layer B220 away from the support layer B210. It can be understood that in some other examples, the metal layer B220 can also be disposed on one surface of the support layer B210. In the conductive composite current collector B200, the thickness and material of the support layer B210, the metal layer B220, and the PTC primer layer B230 are as described above and will not be repeated here.

[0096] like Figure 2 As shown, in the conductive composite current collector B200, the support layer B210 further includes a tab connector 211, the tab connector includes an embedded part 211b and an exposed part 211a connected to the embedded part 211b, the embedded part 211b is embedded in the polymer base film, and the exposed part 211a is located at the periphery of the polymer base film;

[0097] The area of ​​the metal layer B220 corresponding to the exposed part 211a is an inactive area, the area outside the inactive area is an active area, and the PTC base coating layer B230 is located on the active area.

[0098] In this application, if Figure 2 As shown, the conductive composite current collector B200 has a first direction Z and a second direction X. The direction indicated by the first direction Z is the thickness direction of the conductive composite current collector B200. The thickness of the support layer B210, the metal layer B220 and the PTC primer layer B230 refers to the size of the corresponding film layer in the first direction Z. The direction indicated by the second direction X is the width direction of the conductive composite current collector B200. The polymer base film and the tab connector 211 are arranged along the first direction X, and the active area and the inactive area are arranged along the first direction X.

[0099] In traditional composite current collectors, the thickness of the polymer layer accounts for more than 50% of the thickness of the entire composite current collector, which affects the welding quality between the composite current collector and the tab, causing cold welding or false welding. Therefore, it is necessary to weld metal foil on both sides of the polymer layer by ultrasonic transfer welding to improve the welding quality between the composite current collector and the tab. However, this method has complicated and cumbersome procedures, low production efficiency, and as the number of laminated layers increases, the thickness of the battery cell also increases significantly, which is not conducive to improving the energy density of the battery.

[0100] The present application sets a tab connector 211 in the support layer B210, and the tab connector 211 includes an embedded part 211b and an exposed part 211a that are connected to each other. Among them, the embedded part 211b is embedded in the polymer base film, which improves the bonding strength between the polymer base film and the tab connector 211; the exposed part 211a is located at the periphery of the polymer base film, which is conducive to improving the welding quality between the conductive composite current collector B200 and the tab. Through the setting of the tab connector 211, the conductivity and current capacity at the tab can be improved, the rate performance of the battery can be improved, and the subsequent transfer welding process can be reduced to improve production efficiency.

[0101] At the same time, the area of ​​the metal layer B220 corresponding to the exposed part is an inactive area, which is used for subsequent welding of the tabs; the area outside the inactive area of ​​the metal layer B220 is an active area, and the PTC bottom coating B230 is located on the active area. In this way, the safety performance of the conductive composite current collector can be effectively improved, and the welding effect between the conductive composite current collector and the tabs can be improved.

[0102] In the present application, the number of the tab connectors 211 in the support layer B210 may be one or more. Figure 2As shown, the support layer B210 includes two oppositely disposed tab connectors 211, and in the subsequent die-cutting process of the pole piece, it can be ensured that at least one side of the pole piece retains the tab connector 211. However, the present application is not limited thereto, and in some other examples, the support layer B210 may be provided with only one tab connector 211, or may be provided with more than two tab connectors 211.

[0103] In some embodiments, the material of the tab connector 211 includes at least one of stainless steel, copper, nickel and aluminum. Further, the material of the tab connector 211 is the same as the material of the metal layer B220. As a result, the tab connector 211 has high conductivity and good processability, is easy to weld with the tab, and can improve the conductivity and current capacity of the tab, thereby improving the rate performance of the battery cell.

[0104] In some embodiments, in the tab connector 211 , the thickness of the embedded part 211 b is less than the thickness of the exposed part 211 a , and the thickness of the exposed part 211 a is not less than the thickness of the polymer-based film.

[0105] In some embodiments, in the tab connector 211 , the thickness of the exposed portion 211 a is 4 μm to 10 μm, including but not limited to 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0106] In some embodiments, the width of the exposed portion 211a is 2 cm to 8 cm, including but not limited to 2 cm, 3 cm, 4 cm, 5 cm, 6 cm, 7 cm or 8 cm.

[0107] In some embodiments, the width of insert 211b is 2 cm to 12 cm, including but not limited to 2 cm, 3 cm, 4 cm, 5 cm, 6 cm, 8 cm, 7 cm, 8 cm, 9 cm, 10 cm, 11 cm or 12 cm.

[0108] In some embodiments, the insert 211 b has a fence structure to increase the contact area between the insert 211 b and the polymer-based film, thereby improving the bonding strength between the tab connector 211 and the polymer-based film.

[0109] In a second aspect of the present application, a method for preparing a conductive composite current collector is provided, which is used to prepare the conductive composite current collector as described above.

[0110] See also Figure 3 , which is a schematic diagram of a process for preparing a conductive composite current collector in an embodiment of the present application. Figure 3 As shown, the method for preparing the conductive composite current collector comprises the following steps:

[0111] S1: melt-blending a polymer resin and conductive fibers, casting the obtained mixture, wherein the polymer resin forms a polymer base film, and the conductive fibers are dispersed in the polymer base film to obtain a support layer;

[0112] S2: forming a metal layer on at least one surface of the support layer;

[0113] S3: coating a dispersion containing a conductive polymer and a conductive agent on the metal layer, and obtaining a PTC primer layer after drying.

[0114] The following is a detailed description of the preparation method of the conductive composite current collector in a step-by-step manner.

[0115] S1: melt-blending a polymer resin and conductive fibers, casting the obtained mixture, wherein the polymer resin forms a polymer base film, and the conductive fibers are dispersed in the polymer base film to obtain a support layer.

[0116] In some embodiments, the temperature of melt blending is 180°C to 450°C, including but not limited to 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C or 450°C.

[0117] In some embodiments, the melt blending time is 0.5 h to 8 h, including but not limited to 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h.

[0118] In some embodiments, casting the obtained mixture into shape also includes the following steps: setting a tab connector on the inner periphery of the mold, the tab connector including an embedded part and an exposed part connected to the embedded part; casting the mixture obtained by melt blending into the mold and immersing the embedded part, cooling and molding, and obtaining a support layer.

[0119] S2: forming a metal layer on at least one surface of the support layer.

[0120] In some embodiments, the method for preparing the metal layer includes magnetron sputtering.

[0121] In some embodiments, the conditions for preparing the metal layer by magnetron sputtering include: the sputtering atmosphere is an inert gas, the sputtering pressure is 0.5Pa~5Pa, and the sputtering power is 100W~200W. The sputtering atmosphere includes at least one of helium, neon, argon, krypton and xenon; the sputtering pressure can be 0.5Pa, 1Pa, 1.5Pa, 2Pa, 2.5Pa, 3Pa, 3.5Pa, 4Pa, 4.5Pa or 5Pa; the sputtering power can be 100W, 110W, 120W, 130W, 140W, 150W, 160W, 170W, 180W, 190W or 200W.

[0122] In some specific examples, the metal layer is prepared by magnetron sputtering, including the following steps: placing the support layer in a cavity, evacuating the cavity to a vacuum of ≤5×10 -5 Pa, argon gas is introduced at a flow rate of 50 sccm~100 sccm, and DC magnetron sputtering coating is carried out under the conditions of sputtering gas pressure of 0.5 Pa~5 Pa and sputtering power of 100 W~200 W to form a metal layer.

[0123] S3: coating a dispersion containing a conductive polymer and a conductive agent on the metal layer, and obtaining a PTC primer layer after drying.

[0124] In some embodiments, the method for preparing the dispersion includes the following steps: dissolving a conductive polymer in an organic solvent to obtain a polymer solution; adding a conductive agent and performing ultrasonic dispersion to obtain a dispersion.

[0125] In some embodiments, the organic solvent in the dispersion includes at least one of toluene, chloroform, and N-methylpyrrolidone (NMP).

[0126] In some embodiments, the mass fraction of the conductive polymer in the polymer solution is 1% to 5%, including but not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.

[0127] In some embodiments, the ultrasonic dispersion time is 0.5 h to 3 h, including but not limited to 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0128] In some embodiments, coating includes at least one of spin coating, doctor blading, dip coating, spray coating, and drop coating.

[0129] In some embodiments, the drying may be at least one of normal pressure drying, vacuum drying and supercritical drying. Further, the drying is vacuum drying.

[0130] In some embodiments, the vacuum drying temperature is 60°C to 100°C, including but not limited to 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C.

[0131] In some embodiments, the vacuum drying time is 24 h to 48 h, including but not limited to 24 h, 26 h, 28 h, 30 h, 32 h, 34 h, 36 h, 38 h, 40 h, 42 h, 44 h, 46 h or 48 h.

[0132] In some embodiments, coating a dispersion containing a conductive polymer and a conductive agent on the metal layer comprises the following steps:

[0133] The area of ​​the metal layer corresponding to the exposed part is the inactive area, and the area outside the inactive area is the active area. A dispersion containing a conductive polymer and a conductive agent is coated on the active area.

[0134] In a third aspect of the present application, a secondary battery is provided, which includes the conductive composite current collector as described above.

[0135] In the present application, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions (such as Li + 、Na + , K + ) is inserted and removed back and forth between the positive electrode sheet and the negative electrode sheet. The diaphragm is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time allow active ions to pass through. The electrolyte is between the positive electrode sheet and the negative electrode sheet, mainly to conduct active ions.

[0136] In some embodiments, the positive electrode sheet and / or the negative electrode sheet includes a conductive composite current collector as described above.

[0137] In some embodiments, the positive electrode plate includes the conductive composite current collector as described above and a positive electrode active layer covering at least one surface of the conductive composite current collector; wherein the material of the metal layer in the conductive composite current collector is aluminum.

[0138] In some embodiments, the positive electrode active layer includes a positive electrode active material, the positive electrode active material includes a core and a coating layer coating the core, the core includes at least one of a lithium transition metal oxide and an olivine-structured lithium-containing phosphate, and the coating layer includes a relaxor ferroelectric material.

[0139] In the present application, the relaxor ferroelectric material has a higher dielectric constant than the ferroelectric material. Coating a layer of relaxor ferroelectric material on the surface of traditional lithium transition metal oxides and olivine-structured lithium-containing phosphates can achieve the effect of uniform interface electric and ion fields, reduce the impedance of carrier transmission at the interface, and improve the electrochemical performance of the battery.

[0140] In some embodiments, the core includes at least one of a lithium transition metal oxide and an olivine-structured lithium-containing phosphate. The lithium transition metal oxide includes, but is not limited to: lithium cobalt oxide, such as LiCoO2; lithium nickel oxide, such as LiNiO2; lithium manganese oxide, such as LiMnO2 or LiMn2O4; lithium nickel cobalt oxide; lithium manganese cobalt oxide; lithium nickel manganese oxide; lithium nickel cobalt manganese oxide, such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.1 Mn 0.3 O2 (NCM613), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811); lithium nickel cobalt aluminum oxide, such as LiNi 0.8 Co 0.15 Al 0.05 O2; and modified compounds of the above lithium transition metal oxides. Lithium phosphates with olivine structure include but are not limited to: lithium iron phosphate, such as LiFePO4 (LFP); composite materials of lithium iron phosphate and carbon; lithium manganese phosphate, such as LiMnPO4; composite materials of lithium manganese phosphate and carbon; lithium manganese iron phosphate, such as LiFe 0.5 Mn 0.5 PO4; a composite material of lithium manganese iron phosphate and carbon; and a modified compound of the above-mentioned olivine structured lithium-containing phosphate. The modified compound of each material can be at least one of doping modification and surface coating modification.

[0141] In some embodiments, the cladding layer includes a relaxor ferroelectric material. The relaxor ferroelectric material includes but is not limited to: Ba 0.82 Bi 0.12 TiO3, BBT; Bi6Ti5WO 22 , BTW; Bi5Mg 0.5 Ti 3.5 O 15 , BMT; Bi 4.75 Sm 0.25 Mg 0.5 Ti 3.5 O 15 , BSMT; 0.5BaTiO3-0.5Bi(Mg 2 / 3Nb 1 / 3 )O3, BT-BM; 0.8Bi 0.5 Na 0.5 TiO3-0.2BaTiO3, BNT-BT; 0.955Bi 0.5 Na 0.5 TiO3-0.045Ba(Al 0.5 Ta 0.5 )O3, BNT-BAT; 0.75(0.955Bi 0.5 Na 0.5 TiO3-0.045Ba(Al 0.5 Ta 0.5 )O3)-0.25(0.9CaTiO3- 0.1BiScO3), 0.75(BNT-BAT)-0.25(CT-BS); [(K 0.2 Na 0.8 ) 0.8 Li0 .08 Ba 0.02 Bi 0.1 ] (Nb 0.68 Sc 0.02 Hf 0.08 Zr 0.1 Ta 0.08 Sb 0.04 )O3, KNN-H.

[0142] In some embodiments, the coating layer has a thickness of 10 nm to 50 nm, including but not limited to 10 nm, 20 nm, 30 nm, 40 nm or 50 nm.

[0143] In some embodiments, the method for preparing the positive electrode active material comprises magnetron sputtering.

[0144] In some embodiments, the conditions for preparing the positive electrode active material by magnetron sputtering include: the sputtering atmosphere is an inert gas, the sputtering pressure is 0.1Pa~2Pa, and the sputtering power is 50W~150W. Wherein, the sputtering atmosphere includes at least one of helium, neon, argon, krypton and xenon; the sputtering pressure can be 0.1Pa, 0.2Pa, 0.5Pa, 0.8Pa, 1Pa, 1.2Pa, 1.5Pa, 1.8Pa or 2Pa; the sputtering power can be 50W, 60W, 70W, 80W, 90W, 100W, 110W, 120W, 130W, 140W or 150W.

[0145] In some specific examples, the positive electrode active material is prepared by magnetron sputtering, including the following steps: placing the core in a cavity, evacuating the cavity to 1×10 -5 Pa~6×10 -5Pa, argon gas is introduced at a flow rate of 10sccm~100sccm, and radio frequency (RF) magnetron sputtering coating is carried out under the conditions of sputtering gas pressure of 0.1Pa~2Pa and sputtering power of 50W~150W, so that the relaxor ferroelectric material is coated on the surface of the core to form a coating layer.

[0146] In some embodiments, the positive electrode active layer further comprises a positive electrode conductive agent and a positive electrode binder, wherein the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is (80-95): (2.5-10): (2.5-10), and can further be 90:5:5.

[0147] In some embodiments, the positive electrode conductive agent includes at least one of carbon black, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers, and may further be conductive carbon black (Super-P, SP).

[0148] In some embodiments, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), sodium alginate (SA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), hydrogenated nitrile rubber (HNBR), polytetrafluoroethylene (PTFE) and polyacrylic acid (PAA), and may further be polytetrafluoroethylene (PTFE).

[0149] In some embodiments, the positive electrode sheet is prepared by a dry method, which includes the following steps: dry mixing the positive electrode active material, the positive electrode conductive agent and the positive electrode binder at 60°C for 2h~6h, and then hot pressing them on at least one surface of the conductive composite current collector, and then rolling and cutting to obtain the positive electrode sheet.

[0150] In some embodiments, the negative electrode plate includes the conductive composite current collector as described above and a negative electrode active layer covering at least one surface of the conductive composite current collector; wherein the material of the metal layer in the conductive composite current collector includes at least one of stainless steel, copper and nickel.

[0151] In some embodiments, the negative electrode active layer includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder, wherein the mass ratio of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder is (80-95): (2.5-10): (2.5-10), and can further be 80:10:10.

[0152] In some embodiments, the negative electrode active material includes at least one of a carbon-based material, a silicon-based material, a tin-based material, and lithium titanate. The carbon-based material includes at least one of artificial graphite, natural graphite, graphene, soft carbon, and hard carbon; the silicon-based material includes at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy; the tin-based material includes at least one of elemental tin, tin oxide, and tin alloy.

[0153] In some embodiments, the negative electrode binder includes at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), sodium carboxymethyl cellulose (CMC) and carboxymethyl chitosan (CMCS).

[0154] In some embodiments, the negative electrode conductive agent includes at least one of carbon black, acetylene black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene and carbon nanofibers, and may further be conductive carbon black (Super-P, SP).

[0155] In some embodiments, the preparation method of the negative electrode sheet includes the following steps: dispersing the negative electrode active material, the conductive agent and the binder in a solvent (such as deionized water) to prepare a negative electrode slurry; covering the negative electrode slurry on at least one surface of the conductive composite current collector, and obtaining the negative electrode sheet through drying, rolling and cutting.

[0156] It can be understood that the electrolyte in the secondary battery can be liquid, gel or all-solid. Optionally, the electrolyte adopts an electrolyte solution, which includes an alkali metal salt and an organic solvent. Among them, the alkali metal salt includes lithium salt, sodium salt and potassium salt; the lithium salt includes lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate and lithium tetrafluorooxalate phosphate; sodium salt includes sodium hexafluorophosphate, sodium bisfluorosulfonyl imide, sodium bistrifluoromethanesulfonyl imide; potassium salt includes potassium hexafluorophosphate, potassium bisfluorosulfonyl imide, bistrifluoromethanesulfonyl imide, Potassium imide; the organic solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, trimethyl phosphate, triethyl phosphate, cyclopentane, dimethyl sulfone, methyl ethyl sulfone, diethyl sulfone and diethylene glycol dimethyl ether.

[0157] It is understandable that the separator in the secondary battery can be a porous separator with good chemical stability and mechanical stability; at the same time, the separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without special restrictions. Optionally, the material of the separator includes at least one of glass fiber, non-woven fabric, polyethylene (PE) and polypropylene (PP).

[0158] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly through a winding process or a lamination process, and then injected with an electrolyte to form a battery.

[0159] In some embodiments, the secondary battery may include an outer package for encapsulating the electrode assembly and the electrolyte. The outer package of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package, and the material of the soft package may be an aluminum-plastic film, etc.

[0160] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0161] Example 1

[0162] Referring to Table 1 and Table 2, the preparation method of the secondary battery provided in this embodiment is as follows:

[0163] (1) Preparation of positive electrode sheet:

[0164] (1.1) Preparation of support layer:

[0165] The polymer and the conductive fiber are melt-blended at 300°C and uniformly dispersed at a rotation speed of 1000 rpm for 4 hours to obtain a molten mixed liquid; the tab connectors are arranged on both sides of the mold, and the molten mixed liquid is poured into the mold, cooled and formed to obtain a support layer.

[0166] Wherein, the polymer is polyethylene terephthalate (PET);

[0167] The conductive fiber is composed of carbon nanofiber (CNF) and Cu-Ga-In semi-liquid metal coated on the surface of the carbon nanofiber, with a length of 0.5 mm, a diameter of 10 μm, and an aspect ratio of 50;

[0168] The mass ratio of polymer to conductive fiber is 100:15;

[0169] The material of the tab connector is aluminum, which includes a fixing part embedded in the polymer base film and a connecting part located on the outer peripheral side of the polymer base film. The fixing part has a fence structure, the width of the fixing part is 8 cm, the width of the connecting part is 4 cm, and the thickness of the connecting part is 6 μm.

[0170] The thickness of the support layer was 6 μm.

[0171] (1.2) Preparation of metal layer:

[0172] Place the support layer in the cavity and evacuate to 5×10 -5 Below Pa, argon gas is introduced at a flow rate of 80 sccm, a metal target is used as a sputtering target, and DC magnetron sputtering coating is carried out under the conditions of a sputtering gas pressure of 2 Pa and a sputtering power of 150 W to sputter to form a metal layer on both surfaces of the support layer.

[0173] The material of the metal layer is aluminum, and the thickness is 1 μm.

[0174] (1.3) Preparation of PTC primer:

[0175] The conductive polymer is dissolved in toluene to obtain a polymer solution with a mass fraction of 4%; the conductive agent is added to the polymer solution and ultrasonically dispersed for 2 hours to obtain a dispersion; an active area and a tab connection area are preset on the metal layer, and the tab connection area corresponds to the connection part of the tab connector, and then the dispersion is scraped on the active area of ​​the metal layer, and vacuum dried at 80°C for 48 hours to obtain a PTC primer layer, thereby obtaining a conductive composite current collector.

[0176] Among them, the conductive polymer is poly(3-dodecylthiophene-3-hexyl-3-triethylene glycol) (PDDHEO);

[0177] The conductive agent is Super-P (SP), and the mass ratio of the conductive polymer to the conductive agent is 100:35;

[0178] The thickness of the PTC primer layer was 2 μm.

[0179] (1.3) Preparation of positive electrode active materials:

[0180] Place the core in the chamber and evacuate to 5×10 -5 Below Pa, argon gas is introduced at a flow rate of 20 sccm, and relaxor ferroelectric material is used as the sputtering target. RF magnetron sputtering coating is carried out under the conditions of sputtering gas pressure of 0.2 Pa and sputtering power of 60 W to sputter to form a coating layer on the surface of the core.

[0181] Among them, the kernel is NCM 811 , the relaxor ferroelectric material is Ba 0.82 Bi 0.12 TiO3 (BBT), thickness is 30nm.

[0182] (1.5) Preparation of positive electrode sheet:

[0183] The positive electrode active material, binder PTFE and conductive agent SP were dry mixed at a mass ratio of 90:5:5 at 60° C. for 4 hours, and then hot-pressed on the PTC primer layer of the conductive composite current collector. After rolling and cutting, the positive electrode sheet was obtained.

[0184] (2) Preparation of negative electrode sheet:

[0185] (2.1) Preparation of support layer:

[0186] The polymer and the conductive fiber are melt-blended at 220°C and uniformly dispersed at a rotation speed of 1000 rpm for 4 hours to obtain a molten mixed liquid; the tab connectors are arranged on both sides of the mold, and the molten mixed liquid is poured into the mold, cooled and formed to obtain a support layer.

[0187] Wherein, the polymer is polypropylene (PP);

[0188] The material and amount of the conductive fiber are the same as those in step (1.1);

[0189] The material of the tab connector is copper, which includes a fixing part embedded in the polymer base film and a connecting part located on the outer peripheral side of the polymer base film. The fixing part has a fence structure, the width of the fixing part is 8 cm, the width of the connecting part is 4 cm, and the thickness of the connecting part is 4.5 μm.

[0190] The thickness of the support layer was 4.5 μm.

[0191] (2.2) Preparation of metal layer:

[0192] Place the support layer in the cavity and evacuate to 5×10 -5 Below Pa, argon gas is introduced at a flow rate of 60 sccm, a metal target is used as a sputtering target, and DC magnetron sputtering coating is carried out under the conditions of a sputtering gas pressure of 1.5 Pa and a sputtering power of 180 W to sputter to form a metal layer on both surfaces of the support layer.

[0193] The metal layer is made of copper and has a thickness of 1 μm.

[0194] (2.3) Preparation of PTC primer: Same as step (1.3).

[0195] (2.4) Preparation of negative electrode sheet:

[0196] The negative electrode active material graphite (Gr), the binders CMC and SBR, and the conductive agent SP are dispersed in deionized water in a mass ratio of 80:4:6:10, and the negative electrode slurry is obtained after homogenization; the negative electrode slurry is coated on the PTC base coating of the conductive composite current collector, and the negative electrode sheet is obtained after drying, rolling and cutting.

[0197] (3) Assembling secondary batteries:

[0198] In a glove box (Ar atmosphere, water and O2 content <0.1ppm), the positive electrode, glass fiber separator and negative electrode are encapsulated with aluminum-plastic film and injected with electrolyte to make a laminated soft-pack battery cell; the electrolyte includes 1 mol / L LiPF6 and an organic solvent (EC and EMC in a volume ratio of 1:1).

[0199] Embodiments 2 to 11

[0200] Embodiments 2 to 8 are substantially the same as Embodiment 1, except that:

[0201] Example 2: The mass ratio of polymer to conductive fiber is 100:10;

[0202] Example 3: The mass ratio of polymer to conductive fiber is 100:5;

[0203] Embodiment 4: The conductive fiber is a carbon nanofiber, and there is no semi-liquid metal coating on its surface;

[0204] Example 5: Conductive fibers are composed of silver nanofibers (Ag NF) and MXene materials (Ti3C2T x ) with a length of 0.5 mm, a diameter of 10 μm, and an aspect ratio of 50;

[0205] Example 6: In the PTC primer layer, the mass ratio of the conductive polymer to the conductive agent is 100:25;

[0206] Example 7: In the PTC primer layer, the mass ratio of the conductive polymer to the conductive agent is 100:15.

[0207] Example 8: The PTC primer layer includes poly(3-octylpyrrole):poly(styrenesulfonic acid), PVDF and SP in a mass ratio of 95:5:25.

[0208] Example 9: In the positive electrode active material, the material of the coating layer is BTW.

[0209] Example 10: In the positive electrode active material, the material of the coating layer is KNN-H.

[0210] Example 11: The positive electrode active material is NCM 811 , no coating treatment is done.

[0211] Comparative Examples 1 to 4

[0212] Comparative Examples 1 to 4 are substantially the same as Example 11, except that:

[0213] Comparative Example 1: No conductive fiber was added to the support layer, and no PTC primer layer was provided;

[0214] Comparative Example 2: No conductive fiber was added to the support layer;

[0215] Comparative Example 3: No PTC primer layer is provided;

[0216] Comparative Example 4: The conductive polymer of the PTC primer layer is replaced with PVDF of equal mass.

[0217] Table 1. Positive electrode

[0218]

[0219] Note: The mass ratio A refers to the mass ratio of the polymer base film and the conductive fiber, and the mass ratio B refers to the mass ratio of the conductive polymer, the binder and the conductive agent; the thickness of the support layer is 6μm, and the support layer is provided with aluminum tab connectors; the metal layer adopts an aluminum layer with a thickness of 1µm; the thickness of the PTC primer layer is 2μm.

[0220] Table 2. Negative electrode

[0221]

[0222] Note: Mass ratio A refers to the mass ratio of polymer base film and conductive fiber, and mass ratio B refers to the mass ratio of conductive polymer, binder and conductive agent; the thickness of the support layer is 4.5μm, and copper tab connectors are provided in the support layer; the metal layer adopts a copper layer with a thickness of 1µm; the thickness of the PTC primer layer is 2μm.

[0223] Test Case

[0224] The following tests were performed on each embodiment and each comparative example:

[0225] (1) Conductivity of the PTC base coating: Place the conductive composite current collector on the workbench of a four-probe conductivity tester so that the probes accurately contact the PTC base coating and directly read the conductivity data of the PTC base coating at room temperature.

[0226] (2) Battery lift-to-resistance ratio: After the battery is fully charged, its internal resistance values ​​R1 and R2 are tested at 25°C and 120°C respectively, and the battery lift-to-resistance ratio is calculated based on R2 / R1.

[0227] (3) Room temperature cycle test: The battery is subjected to a room temperature cycle test at 2C / 2C, and the battery's first discharge specific capacity at 2C and the number of cycles at which the capacity decays to 80% are recorded.

[0228] The above test results are shown in Table 3.

[0229] Table 3. Conductive composite current collector and battery performance

[0230]

[0231] It can be seen from Table 3 that in Examples 1 to 11, the conductivity of the PTC primer layer at room temperature is 17S / cm to 32S / cm, which is significantly higher than the conductivity of the PTC primer layer of Comparative Example 4 at room temperature, indicating that the use of the PTC primer layer of Examples 1 to 11 is beneficial to improving the conductive properties of the conductive composite current collector. At the same time, in the positive electrode sheet, the tensile strength of the conductive composite current collector is 178MPa~195MPa, and the peel strength of the positive electrode sheet is 14.9N / 25mm~15.4N / 25mm; in the negative electrode sheet, the tensile strength of the conductive composite current collector is 184MPa~207MPa, and the peel strength of the positive electrode sheet is 7.1N / 25mm~8.2N / 25mm, indicating that the conductive composite current collectors of Examples 1~11 have the advantage of high tensile strength, and the introduction of the PTC primer layer increases the surface roughness of the conductive composite current collector, improves the adhesion of the electrode active material layer on the conductive composite current collector, increases the peel strength of the positive electrode sheet and the negative electrode sheet, maintains structural stability during multiple charge and discharge cycles, and thus improves the cycle performance of the battery.

[0232] After being assembled into a battery, the rise-to-resistance ratio from 25°C to 120°C is 5.48~9.74, proving that the internal resistance of the battery cell at high temperatures increases significantly, which can suppress abnormal loop currents and effectively reduce the probability of thermal runaway of the battery at high temperatures. The battery's first discharge capacity at 2C is 186mAh / g~195mAh / g, and the number of cycles for the capacity to decay to 80% is 643~953 times, which has the advantages of high specific capacity and good cycle performance.

[0233] The difference between Examples 1 to 3 lies in the amount of conductive fiber used in the support layer. As the amount of conductive fiber used decreases, the lift-to-resistance ratio from 25°C to 120°C increases, but the discharge specific capacity and cycle number of the battery decrease, indicating that increasing the amount of conductive fiber used in the support layer can improve the capacity and cycle performance of the battery, but will reduce the safety performance of the battery.

[0234] Compared with Example 1, the conductive fibers in the support layer of Example 4 use carbon fibers without a conductive layer, and the lift-to-drag ratio increases, while the discharge specific capacity and cycle performance decrease. This shows that covering the surface of traditional carbon fibers with a conductive layer can also help improve the capacity and cycle performance of the battery.

[0235] Compared with Example 1, the conductive fibers in the support layer of Example 5 and the materials of the conductive layer are different, but the lift-to-drag ratio, discharge specific capacity and cycle performance are not much different from those of Example 1.

[0236] The difference between Examples 1, 6 and 7 lies in the content of the conductive agent in the PTC primer layer. As the content of the conductive agent decreases, the conductivity of the PTC primer layer at room temperature decreases, and the lift-to-drag ratio, discharge specific capacity and cycle performance are significantly reduced, which proves that using a suitable content of conductive agent in the PTC primer layer is crucial to improving the capacity, cycle performance and safety performance of the battery.

[0237] Compared with Example 6, the conductive polymer in the PTC primer layer of Example 8 is different, and a small amount of PVDF is added as a binder, resulting in a slight decrease in the conductivity of the PTC primer layer, but the lift-to-drag ratio, discharge specific capacity and cycle performance are not much different from those of Example 6.

[0238] The difference between Examples 1, 9 and 10 is that different relaxor ferroelectric materials are used in the coating layer of the positive electrode active material. Compared with Example 11 without a coating layer, the discharge specific capacity and cycle performance of Examples 1, 9 and 10 are significantly improved, indicating that the use of relaxor ferroelectric materials to coat traditional ternary positive electrode materials is beneficial to improving the capacity and cycle performance of the battery.

[0239] Compared with Example 1, Comparative Example 1 uses a traditional composite current collector, and its capacity, cycle performance and safety performance are very poor. The support layer of Comparative Example 2 does not add conductive fibers, resulting in low conductivity and mechanical strength of the composite current collector, thereby affecting the cycle performance of the battery. Comparative Example 3 does not have a PTC primer layer, and the adhesion between the electrode material coating and the current collector deteriorates, and the peel strength deteriorates, resulting in reduced safety and cycle performance of the battery. The PTC primer layer of Comparative Example 4 uses PVDF instead of conductive polymer, resulting in reduced safety performance of the battery and deteriorated cycle performance.

[0240] In summary, the conductive composite current collector designed in this application integrates excellent mechanical properties and conductive properties, which helps to ensure the cycle stability of the battery under 2C rate charge and discharge conditions. When the temperature inside the battery cell rises abnormally, the PTC bottom coating can respond quickly, increase resistance, suppress abnormal loop current, and effectively reduce the probability of thermal runaway of the battery at high temperature, thereby improving the safety performance of the battery.

[0241] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0242] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.

Claims

1. A conductive composite current collector, characterized in that: The invention comprises a supporting layer, a metal layer disposed on at least one surface of the supporting layer, and a PTC primer layer disposed on a surface of the metal layer away from the supporting layer; The support layer includes a polymer base film and conductive fibers dispersed in the polymer base film; The PTC primer layer includes a conductive polymer and a conductive agent dispersed in the conductive polymer.

2. The conductive composite current collector according to claim 1, characterized in that: The conductive fiber comprises a fiber and a conductive layer supported on the fiber; The fibers include at least one of carbon fibers, conductive polymer fibers, and metal fibers; The material of the conductive layer includes at least one of semi-liquid metal, high entropy alloy and Mxene material.

3. The conductive composite current collector according to claim 2, characterized in that: The support layer satisfies at least one of the following conditions: (1) The material of the polymer base film includes at least one of polyethylene, polypropylene, polyimide, polyvinyl chloride, polystyrene, polyvinyl alcohol, polyethylene terephthalate and polybutylene terephthalate; (2) The mass ratio of the polymer base film to the conductive fiber is 100:(1-30); (3) The thickness of the support layer is 4 μm to 10 μm.

4. The conductive composite current collector according to claim 1, characterized in that: The PTC primer layer satisfies one or more of the following conditions: (1) The conductive polymer comprises at least one of poly (3-hexylthiophene), poly (3-dodecylthiophene), poly (3-dodecylthiophene-3-hexyl-3-triethylene glycol) and poly (3-octylpyrrole): poly (styrene sulfonic acid); (2) The conductive agent includes at least one of carbon black, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers and metal particles; (3) The mass ratio of the conductive polymer to the conductive agent is 100:(1-50); (4) The thickness of the PTC primer layer is 0.5 μm to 3 μm; (5) The electrical conductivity of the PTC primer layer at room temperature is 10S / cm~40S / cm.

5. The conductive composite current collector according to claim 1, characterized in that: The metal layer satisfies at least one of the following conditions: (1) The material of the metal layer includes at least one of stainless steel, copper, nickel and aluminum; (2) The thickness of the metal layer is 0.5 μm to 4 μm.

6. The conductive composite current collector according to any one of claims 1 to 5, characterized in that: The support layer further includes a tab connector, the tab connector includes an embedded part and an exposed part connected to the embedded part, the embedded part is embedded in the polymer base film, and the exposed part is located at the periphery of the polymer base film; The area of ​​the metal layer corresponding to the exposed part is an inactive area, the area outside the inactive area is an active area, and the PTC primer layer is located on the active area.

7. The conductive composite current collector according to claim 6, characterized in that: The tab connector meets at least one of the following conditions: (1) The material of the tab connector includes at least one of stainless steel, copper, nickel and aluminum; (2) The thickness of the embedded part is smaller than the thickness of the exposed part, and the thickness of the exposed part is not smaller than the thickness of the polymer base film; (3) The width of the embedded part is 2 cm to 12 cm, and the width of the exposed part is 2 cm to 8 cm.

8. A method for preparing a conductive composite current collector according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polymer resin and the conductive fibers are melt-blended and the obtained mixture is cast and molded, wherein the polymer resin forms a polymer base film and the conductive fibers are dispersed in the polymer base film to obtain a support layer; forming a metal layer on at least one surface of the support layer; A dispersion containing a conductive polymer and a conductive agent is coated on the metal layer, and the PTC primer layer is obtained after drying.

9. A battery, characterized in that: Comprising the conductive composite current collector as described in any one of claims 1 to 7.

10. The battery according to claim 9, characterized in that The battery further comprises a positive electrode sheet, wherein the positive electrode sheet comprises the conductive composite current collector and a positive electrode active layer disposed on at least one surface of the conductive composite current collector; The positive electrode active layer includes a positive electrode active material, the positive electrode active material includes a core and a coating layer coating the core, the core includes at least one of a lithium transition metal oxide and an olivine-structured lithium-containing phosphate, and the coating layer includes a relaxor ferroelectric material.

Citation Information

Patent Citations

  • High-safety lithium-ion power battery

    CN108390113A

  • Electrode pole piece and electrochemical device

    CN110676460A

  • Current collector, pole piece and battery

    CN111933953A

  • Composite current collector, preparation method, electrode prepared from composite current collector and battery prepared from composite current collector

    CN114864955A

  • Metal copper composite current collector, preparation method thereof, electrode plate and battery

    CN116454286A

Cited By

  • Functional composite current collector, preparation method thereof and fluorine ion battery

    CN119890319A

  • Functional composite current collector, preparation method thereof, and fluoride ion battery

    CN119890319B

  • Magnesium metal battery based on conductive composite current collector and electric device

    CN120033313A

  • Magnesium metal batteries and electrical devices based on conductive composite current collectors

    CN120033313B

  • Calcium metal battery based on high-conductivity composite current collector and electric device

    CN120237220A